Identification and Expression Analysis of C2H2-Type Zinc Finger Protein (C2H2-ZFP) Genes in Bougainvillea in Different Colored Bracts - Yushan Wang; Yanping Hu; Wen Liu; Wengang Yu; Jian Wang; Yang Zhou (Horticulturae)
Bougainvillea spp. possesses vibrantly pigmented bracts that exhibit high ornamental value. Zinc finger proteins (ZFPs), one of the most extensive transcription factor families in plants, are implicated in diverse biological functions, including plant morphogenesis, transcriptional regulation, and responses to abiotic stress. Nevertheless, their regulatory roles in bract pigmentation in Bougainvillea remain unexplored. In the present investigation, 105 BbZFP genes were identified from the Bougainvillea genome via bioinformatic analyses and subsequently categorized into five subgroups according to the quantity and arrangement of their structural domains. Analysis of physicochemical characteristics demonstrated that the BbZFP family encompasses both acidic and basic proteins, all of which are hydrophilic and predominantly classified as unstable proteins. Gene structure analysis revealed that the majority of BbZFP genes comprise between one and five– introns. Cis-regulatory element analysis suggested that BbZFP promoter regions harbor multiple elements associated with abiotic stress responses, hormonal regulation, and light responsiveness, implying their possible participation in these physiological processes. Transcriptomic data analysis revealed distinct expression patterns of BbZFP genes among bracts of different colors. A quantitative real-time polymerase chain reaction (RT-qPCR) further confirmed that Bou_68928, Bou_1096, Bou_4400, and Bou_17631 were markedly upregulated in yellow bracts relative to white bracts, suggesting their involvement in flavonoid biosynthesis regulation. Meanwhile, Bou_1096 and Bou_17631 exhibited markedly elevated expression in red-purple bracts compared to white bracts, potentially regulating betacyanin biosynthesis in Bougainvillea. These findings offer candidate genes for molecular breeding strategies aimed at enhancing floral coloration in Bougainvillea. The next step will involve elucidating the functions of these genes in bract coloration.